‘Short’ Double-Balloon Enteroscope for Endoscopic Retrograde Cholangiopancreatography in Patients with a Surgically Altered Upper Gastrointestinal Tract - S Cho; P Kamalaporn; G Kandel; P Kortan; N Marcon; G May (Canadian Journal of Gastroenterology)
BACKGROUND: Endoscopic retrograde cholangiopancreatography (ERCP) remains a challenge for endoscopists in patients with surgically altered anatomy of the upper gastrointestinal tract. Double-balloon enteroscopes (DBEs) have revolutionized the ability to access the small bowel. The indication for its therapeutic use is expanding to include ERCP for patients who have undergone small bowel reconstruction. Most of the published experiences in DBE-assisted ERCP have used conventional double-balloon enteroscopes that are 200 cm in length, which do not permit use of the standard ERCP accessories. The authors report their experience with DBE-assisted ERCP using a ‘short’ DBE in patients with surgically altered anatomy.